Embarrassment when illness strikes a close relative: a World Mental Health Survey Consortium Multi-Site Study. Issue 10 (October 2013) - Ahmedani, B. K.; Kubiak, S. P.; Kessler, R. C.; de Graaf, R.; Alonso, J.; Bruffaerts, R.; Zarkov, Z.; Viana, M. C.; Huang, Y. Q.; Hu, C.; Posada-Villa, J. A.; Lepine, J.-P.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Background In this global study we sought to estimate the degree to which a family member might feel embarrassed when a close relative is suffering from an alcohol, drug, or mental health condition (ADMC) versus a general medical condition (GMC). To date, most studies have considered embarrassment and stigma in society and internalized by the afflicted individual but have not assessed family embarrassment in a large-scale study. Method In 16 sites of the World Mental Health Surveys (WMHS), standardized assessments were completed including items on family embarrassment. Site matching was used to constrain local socially shared determinants of stigma-related feelings, enabling a conditional logistic regression model that estimates the embarrassment close relatives may hold in relation to family members affected by an ADMC, a GMC, or both conditions. Results There was a statistically robust association such that subgroups with an ADMC-affected relative were more likely to feel embarrassed compared to subgroups with a relative affected by a GMC (p < 0.001), even with covariate adjustments for age and sex. Conclusions The pattern of evidence from this research is consistent with conceptual models for interventions that target individual- and family-level stigma-related feelings of embarrassment as possible obstacles to effective early intervention and treatment for an ADMC. Macro-level interventions are under way but micro-level interventions may also be required among family members, along with care for each person with an ADMC.